Hierarchical and chemical space partitioning in new intermetallic borides MNi21B20 (M = In, Sn)12. Issue 39 (26th September 2017) - Wagner, Frank R.; Zheng, Qiang; Gumeniuk, Roman; Bende, David; Prots, Yurii; Bobnar, Matej; Hu, Dong-Li; Burkhardt, Ulrich; Grin, Yuri; Leithe-Jasper, Andreas
Abstract : MNi21 B20 (M = ln, Sn): [Ni6 @B20 @Ni24 ] triple shell clusters with M atoms centering the cuboctahedra [M@Ni12 ]. Abstract : The compounds MNi21 B20 (M = In, Sn) have been synthesized and their cubic crystal structure determined (space group Pm 3̄ m, lattice parameters a = 7.1730(1) Å and a = 7.1834(1) Å, respectively). The structure can be described as a hierarchical partitioning of space based on a reo-e net formed by Ni3 species with large cubical, cuboctahedral and rhombicuboctahedral voids being filled according to [Ni1@Ni38 ], [M@Ni312 ], and [Ni26 @B20 @Ni324 ], respectively. The [Ni6 @B20 ] motif inside the rhombicuboctahedral voids features an empty [Ni6 ] octahedron surrounded by a [B20 ] cage recently described in E2 Ni21 B20 (E = Zn, Ga). Position-space bonding analysis using ELI-D and QTAIM space partitioning as well as 2- and 3-center delocalization indices gives strong support to an alternative chemical description of space partitioning based on face-condensed [B@Ni6 ] trigonal prisms as basic building blocks. The shortest B–B contacts display locally nested 3-center B–B–Ni bonding inside each trigonal prism. This clearly rules out the notion of [Ni6 @B20 ] clusters and leads to the arrangement of 20 face-condensed [B@Ni23 Ni33 ] trigonal prisms resulting in a triple-shell like situation Ni26 @B20 @Ni324 ( reo-e ), where the shells display comparable intra- and inter-shell bonding. Both compounds are Pauli paramagnets displaying metallic conductivity.